Protein Profile Study of Some Nigerian Sesame (Sesamum indicum L.) Accessions - Alege, Gbenga Olorunshola (International Journal of Applied Sciences and Biotechnology, 2015)
This study was carried out to investigate the genetic diversity among 23 sesame (Sesamum indicum L.) accessions obtained from different agro-ecological localities from 10 different states across 4 geopolitical zones in Nigeria using evidence from Sodium Dodecyl Polyacrylamide Gel Electrophoresis (SDS-PAGE). Total seed protein of the studied plants resolved on 12% SDS-PAGE showed variations in numbers and intensity of bands among the different sesame accessions. Thirteen (13) major bands were recorded in this study. Lack of unique band and presence of common band (band 7) among the 23 studied sesame accessions indicate some levels of genetic affinity and evidence of common evolutionary origin of the sesame genotypes. This band can therefore be tagged as species specific band for discriminating Sesamum indicum. Cluster analysis grouped the 23 sesame genotypes into two clusters with similarity coefficient ranging from 0.42 to 0.96 which indicates existence of genetic diversity; therefore there is ample opportunity for improving the 23 sesame genotypes. Variations in protein bands observed among the 23 studied plants could be attributed to genomic changes taken place during species diversification. It can be concluded that genetic diversity existed among Nigerian sesame for the improvement of characters of interest. Accessions 9 (YOL), 15(OTT), 22 (OFF) and 23 (JAL) are therefore recommended for used in future breeding programs for the development of improved sesame varieties. Int J Appl Sci Biotechnol, Vol 3(2): 322-329 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.12734